Re-inventing virtual classrooms. How to implement virtual training that meets the needs of modern learners in a corporate environment? - Skrzek, Marcin (Klasy wirtualne zdefiniowane na nowo. Jak wdrażać szkolenia wirtualne w środowisku biznesowym, tak by spełniały oczekiwania współczesnych uczestników?, 2019)
Virtual classrooms continue to grow steadily and play an important role in a corporate learning environment. According to the 2018 Training Industry report 69% of companies use virtual classrooms/webcasting/video broadcasting as one of the components of their digital learning ecosystem. Towards Maturity Health Check report published in Nov. 2018 projects a steady uptake of live online learning over the next 12 months by 55–85%. There are different reasons why organizations decide to implement virtual training. Some examples include the lower cost, ability to reach learners across the globe or effective time management. Regardless of the reason, organizations should apply a structured approach towards the transition to lay the proper foundation and maximize the benefits. The aim of this paper is to present a holistic, end to end virtual classroom strategy definition process which addresses the needs of a modern learner and ensures successful implementation of virtual training. The study is based on a systematic review of the global literature, articles and research in the field of virtual classroom
Management Forum, 2019, vol. 7, no. 1, s. 14-20
Keywords: virtual classroom; virtual training; strategy; modern learner; instructional design; technology; klasa wirtualna; strategia szkoleń wirtualnych; współczesny uczestnik klas wirtualnych; projektowanie szkoleń; technologia